Behind the Legend: A New and Comprehensive Biography of Charles Todd - Holmes, Jim (Journal of Telecommunications and the Digital Economy, 2018)
In 2017 a new biography, Behind the Legend - The Many Worlds of Charles Todd, by Denis Cryle, was published. The biography seeks to provide a more complete understanding of Charles Todd beyond the single achievement for which he became most famous – the building of the Overland Telegraph Line linking Darwin and Adelaide in 1872. The biography lives up to its promise and sets out in considerable detail the contribution that Todd made in many fields during his long lifetime and period of public service. Those fields include astronomy, meteorology, telegraphy, telecommunications more generally, public administration, and contribution to the processes of federal coordination and cooperation. Todd’s fame and legacy have been heavily bound up with the construction of the Overland Telegraph Line. As Cryle notes, he was dubbed ‘Telegraph Todd’ by the media of the day. It is the stated purpose of Cryle’s biography to do justice to Todd across the full range of his achievements. I think that Cryle succeeds admirably. He has written an engaging book that is thoroughly researched and referenced. It will appeal both to historians and to the general reader without expertise in any of the scientific or technical fields inhabited by Todd.